(untitled) (Revista Argentina de Cirugía, 2022)
Enteral nutrition is an important component of advanced life support in the critically ill patient, and has demonstrated to be more physiologic, cheaper and with better results than parenteral nutrition. Jejunostomy for enteral nutrition is indicated when the oral route is impossible and the use of a nasogastric or nasojejunal feeding tube is contraindicated. Although the rate of complications associated with enteral nutrition through jejunostomy is low, they may occur and be serious. We report a case of bowel necrosis associated with a jejunostomy performed for enteral nutrition in a patient who underwent oncologic gastrectomy.